Implementasi Program Pencegahan dan Penanganan HIV/AIDS di Kota Tebing Tinggi - Noflita, Noflita; Ginting, Chrismis Novalinda; Nasution, Sri Wahyuni (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT Indonesian government official reports in 2022 found that more than 543.100 people living with AIDS live in Indonesia, but only 79% of them know their HIV status and only 41,7% took ART drugs. To achieve the United Nations and World Health Organization's 95-95-95 goals, the Indonesian government collaborates with local governments, and local, national, and international organizations, and actively involves the general public. This study aims to assess the implementation of HIV/AIDS prevention and management programs in Tebing Tinggi. This qualitative descriptive study was carried out in the city of Tebing Tinggi and involves ten informants consisting of five key informants (Health Departments’ Communicable Disease Abatement Manager and person in charge in four government-run VCT clinics) and five regular informants (people living with HIV). Data in this study was collected through an in-depth interview with each informant with the help of interview guidelines and constant cross-checking of information among the informants. This study found that implementation of the HIV/AIDS prevention and management programs in Tebing Tinggi was with effective, clear, and consistent communications, adequate staffing and facilities, high compliance and suitable competency, and the existence of SOP and clear hierarchal responsibilities. However, the implementation of these programs remains hampered by inadequate funding, the absence of incentives, and the public reluctance to participate due to the negative stigma. It can be concluded that overall implementation of the HIV/AIDS prevention and management in Tebing Tinggi is relatively good; with some room for improvement for better implementation in the following year. Keywords: AIDS, HIV, Implementation, Policy, Program  ABSTRAK Laporan resmi pemerintah Indonesia pada tahun 2022 menemukan jumlah ODHA di Indonesia mencapai 543.100 jiwa, namun hanya 79% yang mengetahui status HIV-nya dan hanya 41,7% yang menerima ART. Untuk mencapai target 95-95-95 yang ditetapkan Perserikatan Bangsa-Bangsa dan Organisasi Kesehatan Dunia, pemerintah Indonesia bekerja sama dengan seluruh tingkat pemerintahan, organisasi lokal, nasional, dan internasional, serta aktif melibatkan masyarakat. Penelitian ini bertujuan untuk mengetahui implementasi program pencegahan dan penanganan HIV/AIDS di Kota Tebing Tinggi. Penelitian ini merupakan penelitian deskriptif kualitatif yang dilaksanakan di Kota Tebing Tinggi yang melibatkan lima informan kunci (Pengelola Pemberantasan Penyakit Menular Langsung Dinas Kesehatan Kota Tebing Tinggi dan empat penanggung jawab program di klinik VCT milik pemerintah); dan lima informan biasa (ODHIV yang berada di Kota Tebing Tinggi). Data pada penelitian ini dikumpulkan melalui wawancara yang mendalam dengan bantuan alat panduan wawancara. Penelitian ini menemukan bahwa pelaksanaan program pencegahan dan penanganan HIV/AIDS di Kota Tebing Tinggi memiliki komunikasi yang efektif, jelas, dan konsisten, sumber daya manusia dan sarana dan prasarana yang adekuat, kepatuhan yang tinggi disertai kompetensi yang sesuai, serta adanya SOP dan distribusi tanggung jawab yang jelas. Namun, pelaksanaan program-program ini masih dihambat oleh keterbatasan anggaran, tidak tersedianya insentif, serta keengganan masyarakat untuk berpartisipasi dikarenakan stigma negatif terhadap ODHIV. Dapat disimpulkan bahwa pelaksanaan program pencegahan dan penanganan HIV/AIDS di Kota Tebing Tinggi berjalan dengan cukup baik dan masih terdapat ruang untuk peningkatan pengimplementasian yang lebih baik lagi. Kata Kunci: AIDS, HIV, Implementasi, Kebijakan, Program